(untitled) - Black, Uyless D. (New York, 1995)
A new edition of the authoritative source on X.2 facilities, X.1 service, X.25, X.28, and X.29 PAD protocols, internetworking with packet networks and ISDN, telephone and satellite networks, and all X.500 directory applications. Black updates the X series, and the new CCITT X series, embellishing and improving the X.200 recommendations, and adding explanations of APIs and upper level protocols.
Keywords: Giao thức mạng máy tính,Computer network protocols; Tiêu chuẩn,Standards